2018
DOI: 10.4000/rfst.700
|View full text |Cite
|
Sign up to set email alerts
|

Le territoire, générateur d’inégalités face aux cancers

Abstract: Ce document a été généré automatiquement le 6 avril 2021.La Revue francophone sur la santé et les territoires est mise à disposition selon les termes de la Licence Creative Commons Attribution -Pas d'Utilisation Commerciale -Partage dans les Mêmes Conditions 4.0 International.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…In the United States, Yu [ 11 ] found that women living in the most socioeconomically disadvantaged areas have a statistically higher risk of dying from cancer. In France, research has shown that the residents of disadvantaged neighborhoods, or rural areas with low medical density, have less access to screening and are diagnosed with more advanced cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, Yu [ 11 ] found that women living in the most socioeconomically disadvantaged areas have a statistically higher risk of dying from cancer. In France, research has shown that the residents of disadvantaged neighborhoods, or rural areas with low medical density, have less access to screening and are diagnosed with more advanced cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inequalities in cancer prevalence and survival have been widely highlighted by various studies [ 1 , 2 , 3 , 4 ] that have shown social and territorial disparities [ 5 , 6 ]. Other studies have also highlighted inequalities in access to care, particularly with regard to delays in screening and initiation of cancer treatments (surgery, chemotherapy, radiotherapy, etc.)…”
Section: Introductionmentioning
confidence: 99%